"Limits of the Kemeny's Housing Regime Theory" A Comment to Stephens' Paper. Issue 5 (19th October 2020) - Hegedüs, József
ABSTRACT: The comments to Stephens' crucial overview of Kemeny's regime theory, discuss two issues. Firstly, the embeddedness of housing in the political and economic system and its narrowed interpretation. Secondly, the analysis of the socialist and the housing systems of the new EU member states based on Kemeny's approach, which I consider to have low explanatory power and inadequate interpretation of the facts.